1991
DOI: 10.1177/014107689108400612
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Adverse Drug Reaction Reporting Vs Event Monitoring: A Comparison

Abstract: Spontaneous adverse drug reaction (ADR) reporting is the mainstay of national and international drug safety evaluation in the post-approval phase. A major criticism of the method has been a high, but essentially unquantifiable, level of under-reporting by doctors. A direct comparison has been made between spontaneous ADR reporting and an observational event monitoring system for a group of more than 44 000 patients receiving one or other of a group of seven new drugs. The data suggests that underreporting by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 1 publication
0
73
0
2
Order By: Relevance
“…It has been suggested that spontaneous reports of AEs are subject to bias resulting from publicity, prevailing perceptions, and prejudices. 21 Moreover, because mild AEs are less likely to be reported as time passes after product approval and physicians have become more familiar with the drug, the proportion of reported SAEs from the overall total is expected to increase, as is the case in this analysis. Because regional reporting rates for SAEs were in line with global rates, it is likely that non-SAEs may be under-reported more often than SAEs.…”
Section: Discussionmentioning
confidence: 83%
“…It has been suggested that spontaneous reports of AEs are subject to bias resulting from publicity, prevailing perceptions, and prejudices. 21 Moreover, because mild AEs are less likely to be reported as time passes after product approval and physicians have become more familiar with the drug, the proportion of reported SAEs from the overall total is expected to increase, as is the case in this analysis. Because regional reporting rates for SAEs were in line with global rates, it is likely that non-SAEs may be under-reported more often than SAEs.…”
Section: Discussionmentioning
confidence: 83%
“…In Table 2 Probability of receiving at least one report of a coincidental drug-event association when 300 000 patients have been treated during 3 months and the percentage of reported cases r varies from 0. 5 most empirical situations, m is expected to be smaller because of under-reporting and of the generally low background incidence of events potentially unexpected (Type B) reactions. Considering the example of agranulocytosis, under the specified conditions (300, 000 patients treated during 3 months), m equals 0.45 and 0.045 if 100% or 10% of cases were reported, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the interpretation of reported data requires complementary drug utilisation studies before decisionmaking [4]. Thus, the validity of incidence rates calculated on the basis of spontaneously reported data is often questionable and the risks associated with drug treatCorrespondence: Professeur Bernard Begaud, Centre de Pharmacovigilance, H6pital Pellegrin, Batiment IA Nord, 33 076 ments are often underestimated [5]. Conversely, it has been claimed that, in some reported cases, the occurrence of the event during drug treatment may be purely coincidental [6].…”
Section: Introductionmentioning
confidence: 99%
“…AERS, a computerized database which began nearly 40 years ago, is a database containing over 3 million case reports. With the spontaneously reported cases that are stored within the AERS database, the FDA gathers safety data relatively inexpensively to allow the detection of events not seen in clinical trials (1). Exploration of the cases stored within AERS is especially useful for detecting rare events associated with a drug product (2).…”
Section: Fda's Adverse Event Reporting System (Aers)mentioning
confidence: 99%
“…The database contains duplicate reports because more than one person may report the same event. Although duplicate reports may be submitted for some events, a bigger problem with AERS is extensive underreporting, the true extent of which is not known (1). Because busy healthcare practitioners are submitting the bulk of the reports contained within AERS, the quality of the reports is variable; the reports often lack data critical for the evaluation of the event.…”
Section: Fda's Adverse Event Reporting System (Aers)mentioning
confidence: 99%